Early, low-level auditory-somatosensory multisensory interactions impact reaction time speed - Sperdin, Holger F.; Cappe, Céline; Foxe, John J.; Murray, Micah M. (Frontiers in Integrative Neuroscience, 2009)
Several lines of research have documented early-latency non-linear response interactions between audition and touch in humans and non-human primates. That these effects have been obtained under anesthesia, passive stimulation, as well as speeded reaction time tasks would suggest that some multisensory effects are not directly influencing behavioral outcome. We investigated whether the initial non-linear neural response interactions have a direct bearing on the speed of reaction times. Electrical neuroimaging analyses were applied to event-related potentials (ERPs) in response to auditory, somatosensory, or simultaneous auditory-somatosensory multisensory stimulation that were in turn averaged according to trials leading to fast and slow reaction times (using a median split of individual subject data for each experimental condition). Responses to multisensory stimulus pairs were contrasted with each unisensory response as well as summed responses from the constituent unisensory conditions. Behavioral analyses indicated that neural response interactions were only implicated in the case of trials producing fast reaction times, as evidenced by facilitation in excess of probability summation. In agreement, supra-additive non-linear neural response interactions between multisensory and the sum of the constituent unisensory stimuli were evident over the 40-84ms post-stimulus period only when reaction times were fast, whereas subsequent effects (86-128ms) were observed independently of reaction time speed. Distributed source estimations further revealed that these earlier effects followed from supra-additive modulation of activity within posterior superior temporal cortices. These results indicate the behavioral relevance of early multisensory phenomena.